Operating performance analysis of cold and heat sources composite based on ground source heat exchanger and hot water exchange tanks. Issue 1 (1st April 2022) - Miao, Jingquan; Gao, Yan; Liu, Jingru; Cao, Qing; Dou, Huawei; Li, Yanlei; Ji, Fengjun; Zhang, Tao; Li, Yanteng
Abstract: Aiming at the air-conditioning system of underground space engineering, it is proposed to use ground source heat exchanger and hot water exchange tanks in parallel as a composite cold and heat source, which can simultaneously achieve energy-saving requirements. In order to explore the operating heat transfer characteristics of the composite cold and heat source system, a mathematical model of buried pipes and hot water exchange tanks was established. The simulation analysis of the influencing factors such as inlet temperature and fluid flow rate shows that under the condition of small flow rate, increasing the fluid flow rate can significantly improve the buried pipe and the hot water tank and the heat exchange effect; the greater the temperature difference between the inside and outside of the pipe, the better the heat exchange effect of the heat exchanger, under the same flow rate, the heat transfer coefficient of the spiral coil is KDN15 >KDN20 >KDN25 . According to three different load conditions, the flow ratio of the composite cold and heat source is optimized and analyzed. The results show that as long as the flow ratio is properly controlled, the composite cold and heat source can meet the cooling requirements of the air-conditioning system under different working conditions. There is an optimal flow ratio between the heat sources. The greater the ratio R of the extreme working condition load change value to the standard working condition load value, the smaller the value of the optimal flow ratio, and it is not affected by the loop flow rate and the inlet water temperature change.